Startegi Peningkatan Kinerja Karyawan Melalui Komitmen Karyawan Yang Dipengaruhi Oleh Work Life Balance Dan Flexible Working - Khoe Abiel Ivan Rahardjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The Covid-19 pandemic has changed all existing business processes, work no longer has to be bound by time and space. A more flexible way of working is the dream of employees, especially those of the millennial generation. Implementing flexible working is one of the opportunities to increase employee loyalty through employee commitment. Apart from that, many millennial generation employees want balance in life or what is known as work life balance. It is hoped that flexible working and work life balance will foster high work commitment and ultimately encourage employee performance to improve. Based on the hypotheses proposed, all hypotheses are proven and show that employee commitment is able to act as a mediator that strengthens the influence between work life balance and flexible working and employee performance. This research was conducted at the company PT. Alfaria Trijaya with a sample of all of whom are employees under 30 years of age from various departments. Keywords: Work Life Balance, Flexible Working, Employee Commitment, Employee Performance